Short term outcome of radial head arthroplasty in Mason type 3 and 4 fractures - Ganai, Mudasir Rashid; Khan, Shahid Shabir; Rahim, Inayat; Maajid, Saheel; Dar, Tahir Ahmed (International Journal of Research in Orthopaedics, 2021)
Background: Radial head arthroplasty provides a suitable treatment in Mason type 3 and 4 3 fractures. Arthroplasty produces consistent results with a shorter learning curve than ORIF and prevents the late complications associated with radial head excision. Methods: After seeking approval from local institutional ethical committee 30 patients with Mason type 3 and 4 radial head fractures were admitted from outpatient department (OPD) of SKIMS MC and Hospital Bemina, Srinagar. The study was conducted from February 2019 to June 2020 in department of Orthopaedics SKIMS MC and Hospital Bemina, Srinagar. 30 patients with mean age of 25 years comprising of 9 females and 21 males underwent radial head arthroplasty and were followed up to a minimum of 1 year post-operatively. Results: Outcome was evaluated by assessing elbow functional performance using Mayo elbow performance (MEPI). No revisions were performed during the study. Two patients had implant backout and 6 patients had elbow stiffness. Conclusions: Radial head arthroplasty can be used successfully with most of excellent results for treatment of comminuted radial head fracture (Mason type III and IV radial head fractures). Over all radial head arthroplasty is a demanding option in type 3 and type 4 fractures which are not amenable to reconstruction.